Efektivitas Pilates Exercise untuk Mengurangi Nyeri pada Ibu Hamil - Sukmawati Sukmawati; Lilis Mamuroh; Furkon Nurhakim (Malahayati Nursing Journal, 2023)
ABSTRACT Pain incidence  that pregnant women may feel are low back pain, back pain, and even pain during and after childbirth. One way to reduce these incidents is to do light exercise, namely pregnant pilates exercise One way to reduce these events is to do light exercises such as pregnancy pilates. The most widely discussed pregnancy exercise method is Pilates. The aim of a literature review is to identify the benefits of Pilates exercise to reduce pain in pregnant women. The method used is a narrative review with the databases used being PubMed, ScienceDirect, EBSCOhost, SAGE Journals, and Taylor Francis. The research design used in this study was a randomized controlled trial, quasi-experimental, single-blind randomized clinical trial, experimental study design, and case study, in Indonesian and English, published from 2017 to 2022. There were 8  articles discussing the effect of pilates exercise on pain in pregnant women conducted in Indonesian,Turkey, Iran, Korea, Cyprus and Spain. Based on a literature review, pilates exercise can reduce pain in pregnant women such as back pain and also pain during labor. Keywords: Pain In Pregnant Women, Pregnancy Exercise, Pilates Exercise  ABSTRAK Kejadian nyeri yang sering dirasakan ibu hamil adalah nyeri pinggang, nyeri punggung, bahkan  nyeri  selama dan setelah persalinan. Salah satu cara untuk mengurangi kejadian tersebut adalah dengan melakukan olahraga ringan seperti senam hamil. Metode senam hamil yang ramai diperbincangkan adalah Pilates. Tujuan dari tinjauan literatur ini adalah mengidentifikasi manfaat dari latihan pilates untuk menurunkan nyeri pada ibu hamil. Metode yang digunakan adalah narrative review, menggunakan data base  PubMed,  ScienceDirect,  EBSCOhost,  SAGE Journals, dan Taylor Francis. Desain penelitian  yang digunakan pada penelitian ini adalah randomized controlled trial, quasi experimental, single-blind randomized clinical trial, experimental study design dan case study,   berbahasa Indonesia dan inggris, dipublikasikan dari tahun 2017 hingga 2022. Ditemukan 8 artikel yang membahas pengaruh senam pilates terhadap nyeri pada ibu hamil yang dilakukan di Indonesia, Turki, Iran, Korea, dan Indonesia. Berdasarkan tinjauan literatur senam pilates dapat menurunkan nyeri pada ibu hamil seperti nyeri punggung dan juga nyeri pada saat persalinan. Kata Kunci: Nyeri Pada Ibu Hamil, Senam Hamil, Pilates